Examining ozone effects on the tropical C4 crop Sorghum bicolor - Mst Nahid Farha; Flossie Brown; Lucas A. Cernusak; Stephen Sitch; Alexander W. Cheesman (PeerJ)
Ozone (O3), a major air pollutant, can negatively impact plant growth and yield. While O3 impacts have been widely documented in crops such as wheat and soybean, few studies have looked at the effects of O3 on sorghum, a C4 plant and the fifth most important cereal crop worldwide. We exposed grain sorghum (Sorghum bicolor cv. HAT150843) to a range of O3 concentrations (daytime mean O3 concentrations ranged between 20 and 97 ppb) in open-top chambers, and examined how whole plant and leaf morphological traits varied in response to O3 exposure. Results showed no significant impact of realistic O3 exposure on whole plant biomass and its partitioning in sorghum. These findings suggest that sorghum is generally resistant to O3 and should be considered as a favourable crop in O3 polluted regions, while acknowledging further research is needed to understand the mechanistic basis of O3 tolerance in sorghum.